4-PBA ameliorates cellular homeostasis in fibroblasts from osteogenesis imperfecta patients by enhancing autophagy and stimulating protein secretion - Besio, Roberta (Biochim Biophys Acta, 2018)
The clinical phenotype in osteogenesis imperfecta (OI) is attributed to the dominant negative function of mutant type I collagen molecules in the extracellular matrix, by altering its structure and function. Intracellular retention of mutant collagen has also been reported, but its effect on cellular homeostasis is less characterized. Using OI patient fibroblasts carrying mutations in the α1(I) and α2(I) chains we demonstrate that retained collagen molecules are responsible for endoplasmic reticulum (ER) enlargement and activation of the unfolded protein response (UPR) mainly through the eukaryotic translation initiation factor 2 alpha kinase 3 (PERK) branch. Cells carrying α1(I) mutations upregulate autophagy, while cells with α2(I) mutations only occasionally activate the autodegradative response. Despite the autophagy activation to face stress conditions, apoptosis occurs in all mutant fibroblasts. To reduce cellular stress, mutant fibroblasts were treated with the FDA-approved chemical chaperone 4-phenylbutyric acid. The drug rescues cell death by modulating UPR activation thanks to both its chaperone and histone deacetylase inhibitor abilities. As chaperone it increases general cellular protein secretion in all patients' cells as well as collagen secretion in cells with the most C-terminal mutation. As histone deacetylase inhibitor it enhances the expression of the autophagic gene Atg5 with a consequent stimulation of autophagy. These results demonstrate that the cellular response to ER stress can be a relevant target to ameliorate OI cell homeostasis.